Probabilistic Reliability Analysis of Power Systems : A Student's Introduction /: A Student's Introduction. (2020) - Tuinema, Bart W; Rueda Torres, José L; Stefanov, Alexandru I; Gonzalez-Longatt, Francisco M; van der Meijden, Mart A. M. M
No abstract available